KEMAMPUAN MOTORIK KASAR DAN HALUS ANAK USIA 4-6 TAHUN - Cukup Pahala Widi, Sujarwo (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2015)
AbstractThis study begins with the background based on the results of the initial survey of researchers in both interviewswith teachers in kindergarten, that they are difficult to test or measure the students’ motor abilities of their students.In addition they have difficulty in finding a literature review about the instrument made to see gross and fine motorskills to students that age. This study has the objective to look at gross and fine motor skills of student aged 4-6years old. The research method used is survey research. This research is a descriptive technique percentages whichmotor abilities of student aged 4 to 6 years old that kindergarten class A and B were assessed daily by teachers indaily activities or in learning then categorized with 4 categories: BB: Not Growing yet, MB: Start Developing, BSH:Developing Appropriate Hope, BSB: Growing Very Good. The research subjects in this study were all students inkindergarten “Pembina” the District of Bantul totaling 89 student. Research shows that motor skills ability student inkindergarten class A are: in the category is quite high at 53.66%, or 22 student, and high categories 46.34% or 19student. Motor skillsability student in kindergarten class B are: in the category of high enough 12.50% or 6 students,high category 87.50% or 42 student. The conclusion that the motor skills of student aged 4 to 6 years old, especiallyin class A needs to be improved in order to achieve the high category.Keywords: Abilities, Motor Skills, Student 4 to 6 Years Old.AbstrakPenelitian ini diawali dengan latar belakang berdasarkan hasil survei awal peneliti baik wawancara langsung denganguru di Taman kanak-kanak, bahwa mereka kesulitan untuk melakukan tes atau mengukur kemampuan motoriksiswa didik mereka. Selain itu, mereka kesulitan dalam mencari kajian literatur tentang instrumen yang dibuat untukmelihat kemampuan motorik kasar dan halus untuk siswa usia tersebut. Penelitian ini memiliki tujuan untuk melihatkemampuan motorik kasar dan halus anak usia 4 – 6 tahun. Metode penelitian yang akan digunakan adalah penelitiansurvei. Penelitian ini merupakan penelitian deskriptif dengan teknik persentase dimana kemampuan motorik anakusia 4 s.d 6 tahun yaitu TK kelas A dan B yang dinilai sehari-hari oleh guru di dalam aktivitas sehari-hari atau dalampembelajaran kemudian dikategorikan dengan 4 kategori: BB: Belum Berkembang, MB: Mulai Berkembang, BSH:Berkembang Sesuai Harapan, BSB: Berkembang Sangat Baik. Subjek penelitian dalam penelitian ini adalah seluruhsiswa TK Pembina Kecamatan Bantul yang berjumlah 89 anak. Hasil Penelitian menunjukkan bahwa kemampuanmotorik anak di taman kanak-kanak kelas A adalah: dalam katagori cukup tinggi sebesar 53.66% atau 22 anak,dan kategori tinggi 46.34% atau 19 anak. Kemampuan motorik anak di taman kanak-kanak kelas B adalah: dalamkategori cukup tinggi 12.50% atau 6 anak, kategori tinggi 87.50% atau 42 anak. Kesimpulannya bahwa kemampuanmotorik anak usia 4 s.d 6 tahun khususnya di kelas A perlu ditingkatkan agar bisa mencapai kategori tinggi.Kata Kunci: Kemampuan, Motorik, Anak 4 s.d 6 Tahun